2019
DOI: 10.26682/sjuod.2019.22.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Mechanism for Securing Software Defined Network Against Arp Spoofing Attack

Abstract: Software Defined Network SDN is a new emerging paradigm of networking which decouples the data plane and the control plane. It is expected to be a solution to overcome the limitations of traditional networks. Conventional networks had several security problems, some of them disappeared by SDN and some others still exist such as Address Resolution Protocol ARP spoofing. This paper discusses the attacks of ARP spoofing and presents a deep study on the existing solutions either in traditional or SDN environments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…The reference [87] found that by using the MCBLB algorithm in the SDN network, the load balancing is increased by up to 14 %. The authors [5] discussed how to prevent ARP spoofing without using any additional hardware and software but only by extending the SDN controller by a module. The results of the simulation showed that the suggested mechanism is stable against the attack of ARP spoofing.…”
Section: Survey Discussion and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…The reference [87] found that by using the MCBLB algorithm in the SDN network, the load balancing is increased by up to 14 %. The authors [5] discussed how to prevent ARP spoofing without using any additional hardware and software but only by extending the SDN controller by a module. The results of the simulation showed that the suggested mechanism is stable against the attack of ARP spoofing.…”
Section: Survey Discussion and Analysismentioning
confidence: 99%
“…The optimal location of SDN controllers, switches, and other devices is an open challenge in SDN, which affects overall network security and performance [73,74]. Its integration is another security problem because of the design of SDN as it is flat, Where monitoring systems and defense solutions need to be compliant to improve overall performance, energy savings, and network security [5,75]. Fig.…”
Section: Security Challengesmentioning
confidence: 99%
See 3 more Smart Citations